A prospective evaluation of COVID-19 associated coagulopathy with acute coronary syndrome (ACS). (14th October 2021) - Pescetelli, I; Marchetti, M; Gomez Rosas, P; Sanga, E; Russo, L; Moretti, F; Pellegrini, D; Fiocca, L; Canova, P A; Vassileva, A; Gamba, S; Verzeroli, C; et al.
Abstract: Background: Hospitalised COVID-19 pneumonia patients are characterised by the occurrence of a hypercoagulable state associated to a high risk of thromboembolic events. The main laboratory findings of this coagulopathy include D-dimer increase, mild thrombocytopenia, prolonged PT, and increase endothelial activation biomarkers (vWF, thrombomodulin). No data are available about coagulation profile in patients presenting with an acute coronary syndrome (ACS) combined with SARS-CoV-2 infection. Purpose: In this prospective study, we aimed to evaluate the contribute of concomitant SARS-CoV-2 infection to the haemostatic system derangement (i.e., from endothelial cell activation to fibrinolytic phase) observed in patients presenting with ACS. Further, the role of haemostatic biomarkers (HB) for in-hospital mortality risk prediction was also explored. Methods: Consecutive patients admitted to our hospital for ACS at peak intensity of local pandemia were enrolled into this study. At admission, all patients underwent routine blood examinations with blood count, serum biochemical tests and an extensive coagulation profiling. Data from coronary angiography and percutaneous coronary intervention (PCI), when performed, were collected. In-hospital major adverse cardio and cerebrovascular events –MACCEs- (total and cardiovascular death, stroke, systemic or pulmonary embolism, re-MI and bleedings) are reported. Results: A total of 99 (76M/23F) consecutive patients with a median age of 66.7 (±12.1) were enrolled. According to nasal swab, 24 patients were SARS-CoV-2 positive and 75 negative. The two groups, similar in age, sex and cardiovascular risk factors, significantly differed in presenting symptoms (p<.001) and radiological signs of pneumonia (p<.0001). At admission, there were no differences in routine laboratory values between groups. Differently, analysis of the HB showed significantly higher values of D-dimer, vWF antigen, vWF activity and vWF; RiCof, t-PA and PAI-1 and lower levels of ADAMTS-13 in the positive group. Furthermore, among ACS patients, both STEMI and NSTEMI subjects, positive for SARS-CoV-2, had significantly higher plasma values of all the HB compared to the respective negative counterparts, with SARS-CoV-2 positive STEMI subjects displaying the highest values. When performed, PCI finished more frequently with a final TIMI flow <3 (p=.004) in positive patients. The in-hospital rate of MACCEs was 24% (24/99 patients) with a higher (p<.0001) prevalence in SARS-Co-V2 positive group. Cardiovascular mortality accounted for the majority of deaths (8/10; p=.019). At multivariable analysis, we identified dyspnoea at presentation, vWF antigen and leukocyte values as independent risk factors for in-hospital death. Conclusions: In patients presenting with ACS combined with SARS-Cov-2 infection an additional HB asset derangement with stronger endothelial cell activation occurs which negatively impact the outcome, regardless of the invasive treatment. Funding Acknowledgement: Type of funding sources: None.